Pengaruh Pemberian Kompos Daun Gamal (Gliricidia sepium) Terhadap Pertumbuhan dan Hasil Tanaman Tomat (Solanum lycopersicum) - Koti, Kristian; Pakiding, Nobertus Sanda; Limbongan, Yusuf La'lang; Pata'dungan, Adewidar Marano; Driyunitha, Driyunitha (JURNAL AGROPLASMA, 2025)
This study aims to analyze the effect of gamal leaf compost on the vegetative growth of tomato plants, with a focus on improving soil physical and chemical properties, increasing nutrient availability, and reducing dependence on chemical fertilizers. Four treatment combinations were replicated three times, resulting in 12 experimental plots. Each plot consisted of five plants, resulting in a total of 60 tomato plants, effectively increasing tomato growth. The results of this study indicate that the application of 3 kg of gamal leaf compost and 1 kg of soil (B3) significantly impacted tomato growth and yield. This also provides a solution for horticultural farmers and supports sustainable agriculture. Keywords: gamal leaf compost, tomato plants